y - 1 = ⁵/₆(x - 4)
y - 1 = ⁵/₆(x) - ⁵/₆(4)
y - 1 = ⁵/₆x - 3¹/₃
+ 1 + 1
y = ⁵/₆x - 2¹/₃
⁻⁵/₆x + y = ⁵/₆x - ⁵/₆x - 2¹/₃
-6(⁻⁵/₆x + y) = -6(-2¹/₃)
-6(⁻⁵/₆x) - 6(y) = 14
5x - 6y = 14
Month*
divide 840 with 12
as 1 year has 12 months
and you get 70$
so the family spends $70 every month
Its false, standard notation would have an exponent.
Step-by-step explanation:
(x^4)^3=(x^3)^4 , true
=> x^(4×3) = x^(3×4) = x^12
13^4 x 13^7= (13^4)^7, false
13^(4+7) = 13^11
(13^4)^7 = 13^(4×7) = 13^28
y^5 x y^0/y^3=(y^2)^1 , true
y^5 x y^0/y^3 = y^(5+0-3) = y^2
(y^2)^1 = y^(2×1) = y^2
q^0 x q^5/q^2=(q^3)^2/q^3, true
q^0 x q^5/q^2= q^(0+5-2)= q^3
(q^3)^2/q^3 = q^(3×2-3) = q^3
Answer:
41/15
Step-by-step explanation:
I don't know